Laboratory-Modified Argument Driven Inquiry (Lab-Madi) Module: Content Validity Process - Ping, I. L. L.; Osman, K. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
This paper aims to determine the validity of the LAB-MADI module using the Content Validity Index (CVI) and Percentage Calculation Method (PCM). The survey was conducted through the evaluation of six experts via purposive sampling. The instrument used for the evaluation was the content validity instrument. Based on the results of the analysis, the mean scores of CVI and PCM of the LAB-MADI module were 0.97 and 87.22%, respectively while the mean scores of CVI and PCM of eight practical activities based on the seven stages of the MADI model were 0.98 and 81.88% respectively. The results of the study indicate that the module has high validity in the six criteria assessed (suitability for target students, feasibility, time allocation and improving the dependent variables under study: argumentation skills, science process skills and concepts of diffusion and osmosis). Therefore, this module has great potential as a good module. This module is therefore recommended to be used and tested for its effectiveness. The module is also a form of alternative teaching method to guide biology teachers so that they can add value to students in terms of argumentation skills, science process skills and Biology concepts through practical work.